RESPON PETANI TERHADAP KEGIATAN SEKOLAH LAPANGAN PENGELOLAAN TANAMAN TERPADU (SLPTT) DI KECAMATAN AJIBARANG KABUPATEN BANYUMAS - Rifki Andi Novia (MEDIAGRO, 2011)
SLPTT (Sekolah Lapangan Pengelolaan Tanaman Terpadu) is farmer schools with the all activities are in the field, farmers are the owner of the field . By learn on theirs own fields, hopes farmers can figure out theirs problems on theirs farming business also they can solve the problems together. The aim of this research are : (a) to studies farmers responses about SLPTT, (b) to recognize affecting factors about farmer’s responses towards SLPTT activities and (c) to understands affecting applications of cultivation suitable as recommend of SLPTT rice productions improvement.  The research had been held on 2009, in Ajibarang subdistrict, Banyumas district, Central Java province with the samples are farmer who join with SLPTT on 2008/2009 and their main cultivation is rice. The analytic description methode had used in this research as the basic methode, while the stratified random sampling methode had used as a sampling methode with  60  farmers. Some data analysis in this research includes : proportion test for 1st hypothesis, double linear regression analytic for 2nd hypothesis, and simple linear regression for 3rd hypothesis. In this reaserch the final result  which is used propotional analysis proved a little bit of the farmers (>50%) in Ajibarang subdistrict has  good responses about SLPTT activities. The doubled linear regression analysis showed that educations level, being active in farmers group and their  frequency to joined the elucidation influenced the farmer’s responses. Ages, field wide and status from their field have no influenced. And with simple linear regression showed that cultivation applications have no influenced with the rice productions. Keywords : SLPTT,  rice cultivations, farmers response , rice productions